Catching Eyes: Effects of Social and Nonsocial Cues on Attention Capture. (March 2014) - Böckler, Anne; van der Wel, Robrecht P. R. D.; Welsh, Timothy N.
Direct eye contact and motion onset are two powerful cues that capture attention. In the present study, we combined direct gaze with the sudden onset of motion to determine whether these cues have independent or shared influences. Participants identified targets presented randomly on one of four faces. Initially, two faces depicted direct gaze, and two faces depicted averted gaze. Simultaneously with or 900 ms before target presentation, one face with averted gaze switched to direct gaze, and one face with direct gaze switched to averted gaze. When gaze transitions and target presentation were simultaneous, the greatest response-time facilitation occurred at the location of the sudden onset of direct gaze. When target presentation was delayed, direct-gaze cues maintained a facilitatory influence, whereas motion cues induced an inhibitory influence. These findings reveal that gaze cues and motion cues at the same location influence information processing via independent and concurrently acting social and nonsocial attention channels.